Konstruksi Cerita Tolire Gam Jaha Sebagai Sumber Belajar Sejarah Lisan - Zulkifli Zulkifli; Hi. Thalib Abas (Jurnal Ilmiah Wahana Pendidikan, 2022)
Tolire Gam Jaha village which is currently located in the Takome village, West Ternate district and this has become a human memory to this day that the village in ancient times caused the village to sink because it got a curse or disaster because it passed the provisions in conducting a traditional party which then happened. and finally the Tolire village sank and now leaves a legend. Therefore, in this study, to find out how far the students know about "Tolire Gam Jaha" because currently Lake Tolire is taken from the name of the village and has a historical value to be used as a source for learning oral history. Oral history learning resources are human memories (memory) from conversations because historical witnesses or historical actors are not familiar with writing, only relying on conversations that are used every day and this is told from generation to generation because oral history heritage is a source and information to be implemented as a learning resource. on students.